Analisis Kelayakan Finansial Pengolahan Gula Cair Pati Sagu Di Kabupaten Konawe Selatan [Financial Analysis Of Processing Sago Liquid Sugar At South Konawe Regency] - abidin, zainal (Pusat Penelitian dan Pengembangan Perkebunan, 2018)
Sugar is a one of commodity that goverment already decided to reach national self sufficient in 2019. One effort that was conducted is using sago starchto produce liguid sugar. Research was done in Lamokula Village, North Moramo Sub Distric, South Konawe Regency at July – October 2016. The research was conducted to know the economic analysis and organoleptic test of producing liquid sugar from sago starch. Research usedtesting of producion sago liquid sugar in home scale. Besides that organoleptic test was conducted using questionare for 85 panelists that threat the taste, color and smell of sago liquid sugar and also application of sago liquid sugar in drinks. The result of research showed that producing sago liquid sugar from sago starch with capacity 200 kg was feasible with value of RCR 1,79 and net income reach Rp. 1.590.000, with BEP from production side 112 liters and BEP from price side Rp. 10.050. Production of sago liqud sugar still feasible even price of wet sago increase until 30%, gas fuel until 10%, labour and packaging until 20% eventhoug production decrease 10% but price of sago liquid sugar increase minimum 10%. The yield of organoleptic test show that sago liquid sugar have taste, color and smell that can be good accepted by community. Even that if sago liquid sugar apply in fruit ice drinks, the taste and smell of fruit ice drinks is good. For the next sago liquid sugar can substitute sugar cane and also other sweetener and support the the effort to reach national self sufficient of sugar. ABSTRAK Swasembada gula telah dicanangkan oleh pemerintah untuk dicapai tahun 2019. Penelitian dilakukan di Desa Lamokula Kecamatan Moramo Utara Kab. Konawe Selatan pada bulan Juli – Oktober 2016. Penelitian dilakukan untuk mengetahui aspek ekonomi pembuatan gula cair pati sagu dan penerimaan masyarakat terhadap gula cair pati sagu. Penelitian menggunakan uji coba pembuatan gula cair pati sagu. Uji organoleptik dilakukan oleh 85 orang panelis yang menguji tentang rasa, warna dan bau gula cair pati sagu serta pemanfaatannya pada minuman es teler. Hasil analisis menunjukkan bahwa usaha gula cair pati sagu dengan skala 200 kg per bulan layak secara ekonomi dengan nilai RCR 1,79dengan pendapatan bersih per bulan sekitar Rp. 1.590.000, dan nilai TIP sebesar 112 liter dan TIH sebesar Rp. 10.050. Produksi gula cair sagu tetap layak dilaksanakan meskipun terjadi perubahan harga input berupa bahan baku sagu naik hingga 30%, bahan bakar gas hingga 10%, tenaga kerja dan kemasan hingga 20% meskipun produksi turun hingga 10%, akan tetapi harga naik minimal 10%. Hasil uji organoleptik menunjukkan bahwa gula cair sagu memiliki rasa, warna dan bau yang dapat di terima baik oleh masyarakat. Demikian pula halnya jika gula cair sagu digunakan dalam minuman es teler dengan parameter rasa dan bau, di anggap baik oleh panelis. Ke depan gula cair sagu dapat dijadikan sebagai salah satu alternatif dalam upaya pencapaian swasembada gula.